In situ occurrence and protection of crop wild relatives in Italian sites of natura 2000 network: Insights from a data-driven approach - Raggi, Lorenzo; Zucchini, Cecilia; Gigante, Daniela; Negri, Valeria (Frontiers in Plant Science, 2022)
Aim of this work is to evaluate the in situ status of different crop wild relative species in Italy by analysing the geographic distribution of their populations and to suggests possible strategies to improve their future conservation. The work has been focused on different species of the Allium, Beta, Brassica, Secale and Triticum genera that are of priority at European and global levels for the economic importance of the related crops, the level of threat, as well as the potential for use. Geographical distribution and the overall percentage of populations occurring in Natura 2000 sites was initially analysed. In addition, due to the economic importance of the genus and species distribution in Italy, Brassica glabrescens, B. insularis, B. macrocarpa, B. montana, B. procumbens, B. rupestris, B. villosa were the object of additional analyses based on more detailed occurrence data, retrieved from multiple databases, and including land cover/land use and in situ and ex situ density analyses. Using information available in the Italian National Geoportal, geographical distribution data were retrieved for 1,996 in situ populations belonging to 60 crop wild relative species: Allium (43), Brassica (11), Triticum (4), Beta (1)and Secale (1). Percentages of population occurring in Natura 2000 sites are quite different when the different species are considered; this also applies to Brassica species in most need of protection. Results of land cover/land use analysis showed that Brassica populations outside Natura 2000 areas mainly occur in anthropized sites while those within Natura 2000 mainly in sites characterised by natural and seminatural conditions. Areas where genetic reserves could be instituted and that could be the target of future Brassica resources collection missions are also suggested. Based on a large dataset of punctual geographical distribution data of population occurrences across the territory, this research shows that, in Italy, crop wild relatives in situ are in a quite precarious condition especially when species in most need of protection are considered. Our data also highlight the role of Natura 2000 Network in favouring in situ protection of these precious resources in Europe.